Faktor-faktor Risiko Penyalahgunaan Obat pada Remaja - Arief Bachtiar (Jurnal Keperawatan Terapan, 2021)
One of the prevention measures for drug abuse is manipulating the risk factors. This study aims to identify risk factors of drugs abuse and to design an assessment tool of risk factors of drugs abuse. Methodology. The design of study was a case control study with a sample size of 60 respondents in a drugs rehabilitation. The Respondents were divided into 2 groups, each of it consisted of 30 respondents. Samples were obtained by consecutive sampling. Data were collected by questioner and analyzed by Pearson Product Moment and Crombach Alpha Test to examine validity and reability of the instrument. Logistic Regression was used to analyze the risk factors of drugs abuse. Results. The instrument showed good validity and reliability. Findings showed that only family and community factors were associated with drug abuse. While the individual and friend factors became confounding factors. The family factor had four times higher risk than other factors. Conclusion. Our findings suggest the importance of family factor in the prevention of drugs abuse. Morrisikoeover, we suggest to use the assessment of risk factors of drugs abuse as a tool in early detection of drugs abuse prevention.